2010
DOI: 10.1073/pnas.1012540107
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function study of the fourth transmembrane segment of the GABAρ1 receptor

Abstract: The Cys-loop family of receptors mediates synaptic neurotransmission in the central nervous system of vertebrates. These receptors share several structural characteristics and assemble in the plasma membrane as multimers with fivefold symmetry. Of these, the ionotropic GABA receptors are key players in the pathogenesis of diseases like epilepsy, anxiety, and schizophrenia. Different experimental approaches have shed some light on the mechanisms behind the function of these receptors; but little is known about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Next, we examined the role of the residue W475 that our model implicated in the charge stabilization of DPA within the hydrophobic pocket of each GABAr1 subunit. As previously demonstrated, the substitution of W475 by electrically charged amino acids (W475R and W475D) produced nonfunctional receptors, indicating the fundamental role of W475 in the gating of the receptor (Estrada-Mondragón et al, 2010). The substitution of W475 with hydrophobic amino acids (W475F, W475L, W475G, and W475A) produced functional channels with less sensitivity and lower efficacy in response to GABA and faster kinetics, and all of the mutants except W475L demonstrated less cooperativity (as reported by the Hill coefficient) than the WT receptor (Table 1).…”
Section: Fig 2 Noncompetitive Antagonism Of Dpa (A)mentioning
confidence: 59%
See 2 more Smart Citations
“…Next, we examined the role of the residue W475 that our model implicated in the charge stabilization of DPA within the hydrophobic pocket of each GABAr1 subunit. As previously demonstrated, the substitution of W475 by electrically charged amino acids (W475R and W475D) produced nonfunctional receptors, indicating the fundamental role of W475 in the gating of the receptor (Estrada-Mondragón et al, 2010). The substitution of W475 with hydrophobic amino acids (W475F, W475L, W475G, and W475A) produced functional channels with less sensitivity and lower efficacy in response to GABA and faster kinetics, and all of the mutants except W475L demonstrated less cooperativity (as reported by the Hill coefficient) than the WT receptor (Table 1).…”
Section: Fig 2 Noncompetitive Antagonism Of Dpa (A)mentioning
confidence: 59%
“…Interactions between DPA and In Silico Homomeric LGIC Channels. By using the recently published structure of the anionic b3 homomeric human GABA A R (Miller and Aricescu, 2014), we adjusted the previous GABAr1 model (Estrada-Mondragón et al, 2010), which now exhibits a higher alignment score in homology and identity (Supplemental Figs. 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, we were surprised that the p.E375X subunit was incorporated, given that previous studies have shown that TM4 deletion is incompatible with the surface expression of functional ␣1 GlyRs (32)(33)(34)(35). Indeed, the deletion of only a few residues at the C-terminal end of the TM4 domain is sufficient to render some pLGIC receptors completely nonfunctional (12,44,45).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, several key structural elements that determine specific pharmacological response of GABAC receptors have been found [228]. Namely, mutational studies, including those directed toward N-terminal domain and transmembrane domain TM4, have revealed residues that change sensitivity to agonists or make GABAC complex inactive, and contribute to the binding pocket determining properties of GABA binding [221,230,231]. Thus, Tyr102 at ρ1 subunit was identified as part of GABA binding domain, and probably the important residue for coupling agonist binding to channel opening [232].…”
Section: Gabac Receptorsmentioning
confidence: 99%